Accounting Analysis in Household Management A Study of Farmer Families in Bayalangu Lor Village, Gegesik District - Fathan, Rayhan; Rinni Indriyani; Fitriya Sari (Britain International for Academic Research (BIAR) Publisher, 2025)
This study aims to analyze how accounting principles can be applied in household financial management by farming families. The study was conducted in Bayalangu Lor Village, Gegesik District, Cirebon Regency, known to have the highest number of farmers in the area. The research used a descriptive qualitative approach through interviews, observations, and documentation with farming families. The results show that most farmers do not yet use a simple accounting system in managing their household finances, although they acknowledge the importance of recording expenditures and income. The application of simple accounting is believed to help farmers plan budgets, manage debts, and achieve long-term economic stability.